PERSPEKTIF MADZHAB IMAM SYAFI’I RA TERHADAP KADAR HARTA YANG DITERIMA SUAMI DALAM KHULU’ - Aswat, Hazarul; Luthfi, Abdus Salam (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
The level of assets received or iwadh due to the wife's demand for divorce from her husband using the khulu' method, often becomes a prolonged polemic. Referring to the views of the jumhurul ulama, especially the Imam Syafi'i school of thought, which is more of a reference for the Muslim community in Indonesia, makes the marriage dowry that the husband has given to the wife at the time of the marriage contract as redemption for divorce. The main problem in this research is how the legal istinbath is used and what is the opinion of the Imam Syafi'i RA school about the amount of wealth received by the husband in khulu'. The results of this research are that the legal istinbath of the Imam Syafi'i ra school of thought cannot be separated from: Al-Quran, Al-Hadith, Ijma', Kiyas and Istidlal. And the opinion of the Imam Syafi'i school of thought is that a wife is allowed to ask her husband for a divorce, if he is worried that he will not be able to carry out his obligations properly through khulu' means, as well as giving iwadh as ransom. There is no minimum or maximum limit for Iwadh, the wife is allowed to give a ransom which can be equal to the wedding dowry, it can be reduced or it can be more.